Activation of a Non‐Heme FeIII‐OOH by a Second FeIII to Hydroxylate Strong C−H Bonds: Possible Implications for Soluble Methane Monooxygenase. (9th May 2019) - Kal, Subhasree; Que, Lawrence
Abstract: Non‐heme iron oxygenases contain either monoiron or diiron active sites, and the role of the second iron in the latter enzymes is a topic of particular interest, especially for soluble methane monooxygenase (sMMO). Herein we report the activation of a non‐heme Fe III ‐OOH intermediate in a synthetic monoiron system using Fe III (OTf)3 to form a high‐valent oxidant capable of effecting cyclohexane and benzene hydroxylation within seconds at −40 °C. Our results show that the second iron acts as a Lewis acid to activate the iron–hydroperoxo intermediate, leading to the formation of a powerful Fe V =O oxidant—a possible role for the second iron in sMMO. Abstract : Lewis‐saures Fe III aktiviert Fe III ‐OOH : Eine einkernige Nicht‐Häm‐Fe III ‐OOH‐Spezies kann durch Lewis‐saures Fe III (OTf)3 aktiviert werden, um ein starkes Oxidationsmittel zu bilden, das Cyclohexan und Benzol innerhalb von Sekunden bei −40 °C hydroxylieren kann. Dieser Befund liefert nützliche Erkenntnisse über die Chemie des Dieisen‐Enzyms sMMO bei der Umwandlung von Methan in Methanol.